Cost Analysis of Road Congestion Losses on Road Construction (Rigid Pavement) Judging from the Travel Delay Time - Hamdi, Misbakhul; Lubis, Zulkifli (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
Along the duduksampeyan highway there is road construction (rigid pavement) so that the road section has narrowed, which originally had 4 two-way lanes reduced to 2 two-way lanes along 1.5 km so that traffic became paralyzed and caused long queues of vehicles. This results in a significant delay that can harm transportation users who cross the road. The purpose of this study was to determine the length of queues and travel delay times. Then the data that has been obtained from the field is then analyzed based on technical aspects based on the Indonesian road capacity guidelines in 2014 (PKJI, 2014). From the analysis of the queue length above, the longest queue with a length of 2481.3 meters from the direction of Lamongan - Surabaya and the shortest queue with a length of 1187.1 meters in the direction of Lamongan - Surabaya. The results of the delay time analysis found that the highest delay time occurred on Monday at 07:00 – 08:00 with a delay time of 26,26 minutes from the direction of Lamongan - Surabaya and on Wednesday at 08:00 – 09:00 was the lowest delay time with a delay time of 0,1 minutes from the direction of Lamongan - Surabaya.